Parasitoid complex of fall armyworm, spodoptera frugiperda, in Ghana and Benin - Agboyi, L.K.; Goergen, Georg E.; Beseh, P.; Mensah, S.A.; Clottey, V.A.; Glikpo, R.; Buddie, A.; Cafa, G.; Offord, L.; Day, R.; Rwomushana, I.; Kenis, M. (MDPI, 2020)
The fall armyworm, Spodoptera frugiperda, a moth originating from the American continent, has recently invaded most African countries, where it is seriously threatening food security as a pest of cereals. The current management methods rely heavily on the use of synthetic insecticides but there is a need for more sustainable control methods, including biological control. Surveys were conducted in two West African countries, Ghana and Benin, to determine the native parasitoid complex and assess parasitism rates of S. frugiperda. Samples of S. frugiperda eggs and larvae were collected in maize fields located in 56 and 90 localities of Ghana and Benin, respectively, from July 2018 to July 2019. Ten species were found parasitizing the pest, including two egg parasitoids, one egg–larval, five larval and two larval–pupal parasitoids. The two most abundant parasitoids in both countries were two Braconidae: the egg‐larval parasitoid Chelonus bifoveolatus and the larval parasitoid Coccygidum luteum. Parasitism rates were determined in three Ghanaian regions and averages varied from 0% to 75% between sites and from 5% to 38% between regions. These data provide an important baseline for the development of various biological control options. The two egg parasitoids, Telenomus remus and Trichogramma sp. can be used in augmentative biological control and investigations should be conducted to assess how cultural practices can enhance the action of the main parasitoids, C. luteum and Ch. bifoveolatus, in the field. Understanding the parasitoid complex of S. frugiperda in Africa is also necessary before any development of classical biological controls involving the introduction of parasitoids from the Americas.